The Relation between Corporate Social Responsibility and Bank Reputation: A Review and Roadmap - Lorena, Antonio (European Journal of Economics and Business Studies, 2018)
Over the past decades, scholars have paid greater attention to relation between Corporate Social Responsibility (CSR) and corporate reputation. However, despite a growing interest in this area, such linkages have remained relatively unexplored in the banking industry and the precise relationship is not clear. Moving from these considerations, this study proposes a systematic review of peer-reviewed scientific literature aiming to: 1) list, 2) classify and 3) compare existing studies. The review was carried out using the following databases: ISI Web, Google Scholar, and SSRN. I investigate a number of publishing academic works, summarizing main approaches, results and insights. I also provide a roadmap for future study and offer research questions about critical areas of this stream of research. The paper contributes to the ongoing international debates, and the preliminary results are encouraging.